Studentsâ€™ Problems in Implementing Technology Integrated in ELT Classroom - Joko Prayudha (Journal of English Education Program, 2023)
The development of information and communication technology in the world of education has become massive in supporting the advancement of the quality of education. Technology demands fundamental changes in the learning process, so it is necessary to maximize its utilization to support better learning. In learning English, integrating technology is one of the things that English teachers can do to maximize their digital skills and make English communication more balanced for students. This study aims to analyze the problems faced by ELT students in implementing the use of technology in English classes. The method used in this study uses a qualitative-descriptive approach. The research sample is 35 English students who apply learning using technology. Data was collected through observation, interviews, and questionnaires related to the problems that ELT students face when learning English with the help of technology. The results of the study show that there are several problems faced by ELT students in learning English through the use of technology, including the implementation of learning English by integrating technology Â mastery of using learning applications is low, the technology owned by students does not fully support technology-based learning, management time, lack of internet quota, and students find it difficult to understand if only explained once in a while.